Answer: C
Step-by-step explanation: 8 (1/3) 16 (2/3) 24 (3/3)
" Given f (x) = 3x + 2 and g(x) = 4 – 5x, find (f + g)(x), (f – g)(x), (f × g)(x), and (f / g)(x).1. = [3x + 2] + [4 – 5x] = 3x + 2 + 4 – 5x. = 3x – 5x + 2 + 4. = –2x + 6. (f – g)(x) 2. = f (x) – g(x)= [3x + 2] – [4 – 5x] = 3x + 2 – 4 + 5x. = 3x + 5x + 2 – 4. = 8x– 2. 3. ...= (3x + 2)(4 – 5x) = 12x + 8 – 15x2 – 10x. = –15x2 + 2x + 8. " - Google
<span>a2 – b2 = (a + b)(a – b) or (a – b)(a + b).
This is the 'Difference of Squares' formula we can use to factor the expression.
In order to use the </span><span>'Difference of Squares' formula to factor a binomial, the binomial must contain two perfect squares that are separated by a subtraction symbol.
</span><span>x^2 - 4 fits this, because x^2 and 4 are both perfect squares, and they are separated by a subtraction symbol.
All you do here to factor, is take the square root of each term.
√x^2 = x
√4 = 2
Now that we have our square roots, x and 2, we substitute these numbers into the form (a + b)(a - b).
</span>
<span>(a + b)(a - b)
(x + 2)(x - 2)
Our answer is final </span><span>(x + 2)(x - 2), which can also be written as (x - 2)(x + 2), it doesn't make a difference which order you put it in.
Anyway, Hope this helps!!
Let me know if you need help understanding anything and I'll try to explain as best I can.</span>
Answer:
comparison
Step-by-step explanation:
comparison